Infection Strategies and Pathogenicity of Biotrophic Plant Fungal Pathogens - Mapuranga, Johannes; Zhang, Na; Zhang, Lirong; Chang, Jiaying; Yang, Wenxiang (Frontiers in Microbiology, 2022)
Biotrophic plant pathogenic fungi are widespread throughout the world and are responsible for significant crop losses. Biotrophic plant pathogenic fungi grow on or in living hosts where they obtain their nutrients by maintaining the viability of their hosts. The infection processes they parade maneuver physiology of the host to maintain its viability for several days. To facilitate biotrophic invasion, fungal pathogens have sophisticated infection structures, such as appressorium for plant invasion, haustoria for nutrient uptake, secretion of effector proteins, and modulation of host physiology, including suppression of immune response. Several sophisticated mechanisms are involved in fungal-host interactions that enable them to suppress the host defense system and redirect its metabolic flux. Pathogenic effectors are crucial for the manipulation of the host defense system. Different biotrophic pathogenic fungi have different strategies to infect the host plant, and they secrete effectors without any sequence similarity or conserved motif or domain. With the advent of the genomic era, new technologies have been introduced that have accelerated the identification of effectors of biotrophic fungi and their functional characterization. In this review, we discuss the characteristics of biotrophic fungi, infection strategies, and pathogenicity mechanisms of biotrophic plant fungal pathogens.